Immunohistochemical study of non-Hodgkin lymphoma patients in Basrah (Single center experience) - Haider Abdul Hassan ALI; Jasim Mohammed AL-DIAB; Saad Abdulbaqi ALOMAR (Romanian Journal of Medical Practice)
Background. Non-Hodgkin lymphoma (NHL) represents a diverse group of lymphoid tissue cancers, predominantly arising from B-cells, T-cells, or natural killer cells. The accurate diagnosis of NHL subtypes is crucial, given their varying clinical behavior and treatment responses. This study focuses on the application of immunohistochemistry (IHC) in diagnosing and classifying NHL, comparing its efficacy to traditional hematoxylin and eosin (H&E) staining methods. Methods. Conducted at Al-Sadr Teaching Hospital, Basrah, this cross-sectional study involved 48 newly diagnosed NHL cases in 2015. Patients were initially examined using H&E-stained sections from lymph nodes and extranodal tissue biopsies. IHC staining, employing a range of primary antibodies, was then used to confirm diagnoses and subtype NHL cases. Results. The study revealed a predominance of diffuse large B-cell lymphoma (DLBCL) at 50%. Other subtypes that were identified included mantle cell lymphoma, Burkitt lymphoma, lymphoblastic lymphoma, MALToma, peripheral T-cell lymphoma, and follicular lymphoma. The IHC method proved critical in identifying specific NHL subtypes, which were not detectable by H&E staining alone, such as mantle cell lymphomas and peripheral T-cell lymphomas. The study highlighted discrepancies with regional studies, emphasizing variations due to sample size and regional factors. Conclusion. Immunohistochemical staining is an indispensable tool for accurately diagnosing and classifying NHL, complementing H&E staining. This study underscores the need for a comprehensive diagnostic approach, including a panel of antibodies, to optimize the diagnostic process and ensure accurate treatment planning.